(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2019)
The heritage of Yogyakarta is always situated in a dynamic urban environment. Heritage conservation has been challenged by a lack of understanding on the ideological process in the creation of meanings. This paper investigates the creation process of urban space that is currently appreciated as heritage. The paper uses the city of Yogyakarta as the case study because its uniqueness as a mix of traditional and colonial cities. The study uses the concept of meaning production to understand the association between the construction of urban space and ideological meanings. This concept corresponds to the creation of urban objects and the recognition of meanings in the society. This study uses data sourced from a literature study. As the result, the process of meaning production has demonstrated social and political forces in the construction of traditional and colonial buildings. Situation in the past demonstrates urban space as a tool of political hegemony of traditional court and colonialist. A different social milieu in the present day changes the conflicting ideologies into history. Therefore, the urban structure expresses political strategies of relevant authorities in proclaiming hegemony and regulating society. This study provides a basis for investigating the influence of ideologies on the meaning of heritage that corresponds to cultural significant.